1999
DOI: 10.1091/mbc.10.10.3289
|View full text |Cite
|
Sign up to set email alerts
|

Nascent Polypeptide–associated Complex Stimulates Protein Import into Yeast Mitochondria

Abstract: To identify yeast cytosolic proteins that mediate targeting of precursor proteins to mitochondria, we developed an in vitro import system consisting of purified yeast mitochondria and a radiolabeled mitochondrial precursor protein whose C terminus was still attached to the ribosome. In this system, the N terminus of the nascent chain was translocated across both mitochondrial membranes, generating a translocation intermediate spanning both membranes. The nascent chain could then be completely chased into the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 63 publications
5
129
0
1
Order By: Relevance
“…An ideal candidate for this type of control is the nascent polypeptideassociated complex (NAC), which competes with the SRP for binding to polypeptides as they emerge from the translating ribosomes and is thought to negatively regulate protein transport to the ER (35,36). Interestingly, NAC has recently been implicated as an enhancer of protein targeting to the mitochondria (37,38). We suggest a working model (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…An ideal candidate for this type of control is the nascent polypeptideassociated complex (NAC), which competes with the SRP for binding to polypeptides as they emerge from the translating ribosomes and is thought to negatively regulate protein transport to the ER (35,36). Interestingly, NAC has recently been implicated as an enhancer of protein targeting to the mitochondria (37,38). We suggest a working model (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was later suggested that such locus-specific translation may play a marginal role in the mitochondrial import (Suissa and Schatz, 1982), several recent observations support the idea that a cotranslational process is involved in the mitochondrial import of some proteins (reviewed in Verner, 1993;Lithgow, 2000). The discovery, in mammalian cells, of the nascent polypeptide-associated factor NAC (Wiedmann et al, 1994) and the fact that, in yeast, disruption of either the genes encoding the subunits of the NAC complex or its homologue, the ribosome-associated complex (RAC) (Gautschi et al, 2001), leads to defects in protein targeting to mitochondria (George et al, 1998;Funfschilling and Rospert, 1999) confirm that translation and import are associated.…”
Section: Introductionmentioning
confidence: 95%
“…This binding is independent of signal peptide sequences, and yet NAC cooperates with signal recognition particle (SRP) for correctly targeting and folding of nascent polypeptide in the cotranslational process (Lauring et al, 1995a, b;Powers and Walter, 1996;Moller et al, 1998b). However, yeast NAC homolog (termed as EGD complex) is not prerequisite for growth (Reimann et al, 1999), but is necessary for protein targeting to mitochondria (George et al, 1998;Fünfschilling and Rospert, 1999). In addition, in yeast both subunits including their NAC domains have been shown to be ubiquitinated in a lysine dependent manner (Panasenko et al, 2006(Panasenko et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%